Relationships between Septic Tank Construction and Number of Escherichia coli in Dug Well Water in Rahandouna Village, Kendari, Southeast Sulawesi, Indonesia - Bromo Kusumo Achmad; Erwin Azizi Jayadipraja; Sunarsih Sunarsih; Muhammad Abdul Gafur Tirtayasa Mangidi (Journal of Epidemiology and Public Health, 2020)
Background: Dug wells provide water from soil layer that is close to the surface of the soil, therefore it is susceptible to contamination through seepage from human waste, animals, and for domestic household use. This study aimed to determine the relationships between septic tank construction, dug well distance, and number of E. coli in Rahandauna Village, Ken